PENERAPAN MODEL COOPERATIVE LEARNING TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA - Shinta Wardhani, Ratri; Setyaningrum, Dwi; Sugiyanta, Geyol (Elementary School and Education Journal, 2026)
This study aims to improve students’ learning outcomes in the Pancasila Education subject through the implementation of the cooperative learning model Teams Games Tournament (TGT) in Grade III of SD Muhammadiyah Kulur during the 2025/2026 academic year. The research employed a classroom action research (CAR) approach conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were 20 third-grade students. Data were collected through observation, learning achievement tests, and documentation. The findings revealed a significant improvement in the average learning scores from the pre-cycle to the second cycle, as well as an increase in the percentage of students achieving mastery learning. Teacher and student activity also showed positive progress, indicating more interactive and engaging learning. Thus, the TGT model proved effective in enhancing learning outcomes in Pancasila Education and fostering teamwork and sportsmanship among students.